2022
DOI: 10.3390/diagnostics12102417
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Application of Cardiac Magnetic Resonance in ART-Treated AIDS Males with Short Disease Duration

Abstract: Cardiac complications are common in antiretroviral therapy-treated (ART-treated) acquired immune deficiency syndrome (AIDS) patients, and the incidence increases with age. Myocardial injury in ART-treated AIDS patients with a relatively longer disease duration has been evaluated. However, there is no relevant study on whether patients with a short AIDS duration have cardiac dysfunction. Thirty-seven ART-treated males with AIDS and eighteen healthy controls (HCs) were prospectively included for CMR scanning. Cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Hou et al evaluated the cardiac function of antiretroviral therapy-treated (ART-treated) males with AIDS using CMR imaging and found that those with a short disease duration may not develop obvious cardiac dysfunction as evaluated by routine CMR [10]. The findings suggest that routine CMR may not be necessary for ART-treated males with AIDS with a short disease duration, but it is important to consider individual patient characteristics and other factors when determining follow-up intervals.…”
Section: Inflammatory Cardiomyopathymentioning
confidence: 99%
“…Hou et al evaluated the cardiac function of antiretroviral therapy-treated (ART-treated) males with AIDS using CMR imaging and found that those with a short disease duration may not develop obvious cardiac dysfunction as evaluated by routine CMR [10]. The findings suggest that routine CMR may not be necessary for ART-treated males with AIDS with a short disease duration, but it is important to consider individual patient characteristics and other factors when determining follow-up intervals.…”
Section: Inflammatory Cardiomyopathymentioning
confidence: 99%
“…A number of, although not all, echocardiographic studies in PWHIV have shown an increased prevalence of left ventricular (LV) systolic and/or diastolic dysfunction (7)(8)(9)(10)(11). Recent cardiac magnetic resonance imaging (CMR) studies have also shown left ventricular systolic and/or diastolic dysfunction in some (12)(13)(14) but not all studies (15,16). A large study evaluating cardiac chamber volumes in almost 600 PWHIV who were virologically suppressed on ART, and age-and sex-matched controls, using multidetector CT scans to measure cardiac volumes which were then indexed to body surface area (BSA) was reported.…”
Section: Introductionmentioning
confidence: 99%